2021
DOI: 10.23923/rpye2021.01.199
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas de las escalas de variables disposicionales y contextuales (IEPA y AYES) adaptadas a la asignatura Inglés como Lengua Extranjera

Abstract: This study aims to test the validity of the Dispositional Variables (IEPA) scale,which evaluates students' learning interest, progress, and effort, and of the Contextual Variables (AYES) scale,which evaluates whether the teacher helps students to learn, values theireffort, and can arouse their interest in the subject English as a Foreign Language in Compulsory Secondary Education and Higher Secondary Education. Other aims are to determine whether personal variables affect the scale factors and whether contextu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Some results obtained in other studies that used these same instruments have shown that there are motivational differences between subjects, genders and ages. As is the case in a particular study that applied them to the subject of English [19], which found differences in terms of gender, girls had higher scores in terms of interest and effort in this subject, indicating that they have a greater predisposition and attitude towards learning. But in the case of the study by Cecchine et al [15], where he analyzed the differences between subjects such as mathematics, language and communication, and physical education, finding differences between two of them, students had lower scores in mathematics and language and communication, specifically in the dispositional variable "I have interest in learning" and in the contextual variable "the teacher awaken their interest".…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some results obtained in other studies that used these same instruments have shown that there are motivational differences between subjects, genders and ages. As is the case in a particular study that applied them to the subject of English [19], which found differences in terms of gender, girls had higher scores in terms of interest and effort in this subject, indicating that they have a greater predisposition and attitude towards learning. But in the case of the study by Cecchine et al [15], where he analyzed the differences between subjects such as mathematics, language and communication, and physical education, finding differences between two of them, students had lower scores in mathematics and language and communication, specifically in the dispositional variable "I have interest in learning" and in the contextual variable "the teacher awaken their interest".…”
Section: Discussionmentioning
confidence: 79%
“…Although different studies have addressed the relationship between students' dispositional variables-interest, effort and learning progression in different settings, such as school settings [2,5,[14][15][16][17][18][19][20], university [21] and extracurricular and/or sport contexts [22,23]-there are not many instruments that incorporate contextual and dispositional variables in secondary education students. Effort can be a consequence of the pleasure of learning, and in this case, it is situated between progress in learning and the interest of students, for each of whom it has a very different meaning, since they experience it in a positive way.…”
Section: Introductionmentioning
confidence: 99%